2021
DOI: 10.25077/ar.8.1.82-92.2021
|View full text |Cite
|
Sign up to set email alerts
|

Marine Ecolexicon of Noun-Verb of the Coast Community in Pesisir Barus, Central Tapanuli

Abstract: This study aims to describe the lingual form, which is a manifestation of the understanding of the speech community of the environment towards its environmental dimension. The theory used in this research is ecolinguistic. Data in the form of basic lexicons and affixed lexicons related to the marine environment were collected through interviews with informants. Furthermore, the data were analyzed by grouping them based on the word class, environmental category, and the affixation process contained in the affix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The research by Lubis and Widayati (2021) provided a thorough evidence of how Pesisir Barus community reflected their relationship toward marine environment through the lexicons they utter in the interview. The community used to consist of various dialects since Barus was an important trading route even though the major groups were Minangkabau and Batak.…”
Section: Ecolinguistics and Language Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…The research by Lubis and Widayati (2021) provided a thorough evidence of how Pesisir Barus community reflected their relationship toward marine environment through the lexicons they utter in the interview. The community used to consist of various dialects since Barus was an important trading route even though the major groups were Minangkabau and Batak.…”
Section: Ecolinguistics and Language Diversitymentioning
confidence: 99%
“…The research concluded that the linguistic evidence in the interview depicted that Barus community reflects an understanding of the interaction, interrelation, and interdependence of the society and its environment. Human beings are parts of the organisms that are dependent one to another (Lubis & Widayati, 2021).…”
Section: Ecolinguistics and Language Diversitymentioning
confidence: 99%
“…At the same time, combined with the current popular sentence similarity research methods, different methods are used to cluster verb patterns. First, the data preprocessing [33] method is introduced, and then the influence of different text representation methods and clustering algorithms on the verb pattern clustering results is analysed using the WMD model.…”
Section: Clustering Algorithm Based On Wmd Modelmentioning
confidence: 99%
“…These three aspects of how people act in society are about how they use language and interact with their environment. This research has also been reviewed by (Lubis & Widayati, 2021); the study found many words related to the marine environment. These words are categorized into names of things (nouns) and words describing actions (verbs).…”
Section: Introductionmentioning
confidence: 99%